(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2020)
Read is the first word and divine order in the Holy Quran. My lovely physics does not answer many mysteries in the universe including black holes. The observed ordinary matter in the universe is only 5 %. The remaining is 27% dark matter and approximately 68% dark energy of. This paper introduces a developed model and concept to black hole anatomy and entropy-surface area correlation. It considers the stationary black hole a one entity of 4 concentric spheres around the singularity. They are the event horizon, photon sphere at 1.5Rs, unstable light sphere at 2.6Rs and innermost stable particle sphere at 3Rs. An equation (Sayed Ts formula) was derived excluded heuristics of Professor S. Hawking. This formula is based on different proportional constant between entropy and black hole surface area; not ¼ as He conjectured. In spite of my respect and humanity sympathy with Prof. Hawking, his tombstone equation should be corrected. There is neither radiation escape from black holes nor any signal detected due to micro black holes evaporation. Finally, it can be stated that Hawking radiation is Nothing.